IMPLEMENTASI NILAI-NILAI KEPEMIMPINAN TUMENGGUNG DALAM PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR 33/II DI KABUPATEN MUARO JAMBI - Andi Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of Tumenggung leadership values in the character development of students at SD Negeri 33/II, Muaro Jambi Regency. Tumenggung leadership, as one of the local wisdoms of the Suku Anak Dalam (SAD) community, embodies noble values that are relevant to character education, such as responsibility, exemplary behavior, justice, deliberation, social awareness, and environmental concern. This research employed a qualitative approach using a descriptive method. The research informants consisted of the school principal, teachers, students, and community leaders who understand the values of Tumenggung leadership. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that Tumenggung leadership values have been implemented in various school activities, including the learning process, habituation programs, extracurricular activities, and school culture. The implementation of these values can be observed in classroom deliberations, classroom duty schedules, group work activities, mutual cooperation programs, and environmental care initiatives. The application of Tumenggung leadership values has had a positive impact on students’ character development, particularly in improving discipline, responsibility, cooperation, social awareness, and environmental concern. This study demonstrates that local wisdom can serve as an effective learning resource in strengthening character education at the elementary school level while simultaneously contributing to the preservation of local culture amidst the challenges of globalization.